High efficiency hysteresis-less inverted planar heterojunction perovskite solar cells with a solution-derived NiOx hole contact layer. Issue 48 (23rd November 2015) - Yin, Xingtian; Que, Meidan; Xing, Yonglei; Que, Wenxiu
Abstract : A solution-derived NiO x film was successfully employed to work as the hole selective contact for a high efficiency inverted planar heterojunction perovskite solar cell with negligible hysteresis. Abstract : A hysteresis-less inverted planar heterojunction perovskite solar cell with 14.42% power conversion efficiency (PCE) was successfully fabricated by employing a solution-derived NiO x film as the hole selective contact. Here, the non-stoichiometric transparent NiO x film is composed of a lot of small NiO x nanocrystals with a cubic crystal structure. Inverted planar heterojunction perovskite solar cells based on the as-prepared NiO x hole selective contacts show a much higher PCE and air storage stability than the control device fabricated from the PEDOT:PSS film as the hole selective contact, since NiO x has a better electron blocking property due to its high conduction band edge position. The thickness of the NiO x contact strongly influences the performance of the NiO x -based perovskite solar cells, which include the PCE, hysteresis behaviors and air storage stability due to the thickness-dependent morphology of the NiO x contact.